First screening of bacteria assemblages associated with the marine polychaete Melinna palmata Grube, 1870 and adjacent sediments - Menabit, Selma; Lavin, Paris; Begun, Tatiana; Mureşan, Mihaela; Teacă, Adrian; Purcarea, Cristina (Frontiers in Marine Science, 2024)
Bacteria associated with marine invertebrate play a fundamental role in the biology, ecology, development and evolution of their hosts. Although many studies have been focused on the microbial populations of benthic and pelagic habitats, little is known about bacteria colonizing tube-dwelling polychaete. In this context, the current study provided the first characterization of the Melinna palmata Grube, 1870 microbiome based on Illumina sequencing of 16S rRNA gene of the polychaete tissue and proximate sediments collected from the Black Sea, Romania, along a 24.2 m – 45.4 m depth-gradient. The diversity, taxonomic composition and deduced functional profile of the tissue and sediments associated bacterial communities were compared and analyzed in relation with the environmental parameters. This polychaete harbored a distinct bacterial assemblage as compared to their sediments and independent on the depth of their habitat, including 8 phyla in tissues dominated by Proteobacteria, and 12 phyla in sediments majorly represented by Actinobacteriota, respectively. At order level, Synechococcales, Rhodobacterales and Actinomarinales were highly represented in the M. palmata microbiome, while Microtrichales, Anaerolineales and Caldilineales were mostly found in sediments. A significant correlation was observed between Cyanobacteria taxa and the dissolved oxygen concentrations in shallow waters impacted by the Danube inputs. Meanwhile, this phylum showed a positive correlation with Planctomycetota colonizing the invertebrate tissues, and a negative one with Actinobacteriota and Chloroflexi found in sediments. The deduced functional profile of these bacterial assemblages suggested the prevalence of the amino acid and carbohydrate metabolism for both analyzed matrices. This pioneering report on the M. palmata microbiome highlighted the environment contribution to bacterial species enrichment of the polychaete, and provided a glimpse on the putative role of microbial communities associated with this marine organism.